1993
DOI: 10.1111/j.1476-5381.1993.tb13732.x
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Adrenoceptor‐mediated modulation of the nitrergic innervation of the canine isolated ileocolonic junction

Abstract: 1 The effects of specific a-adrenoceptor agonists and antagonists on electrically-evoked non-adrenergic non-cholinergic (NANC) relaxations, previously demonstrated as nitrergic, were investigated in isolated circular muscle strips of the canine ileocolonic junction. 2 During a substance P-induced contraction and in the presence of atropine and guanethidine, the specific a,-adrenoceptor agonist, phenylephrine and antagonist, prazosin, as well as the specific M2-adrenoceptor antagonist, yohimbine, had no effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
(29 reference statements)
2
17
1
Order By: Relevance
“…Transient presynaptic inhibition of nitrergic nerves could be responsible for this, although this has never been demonstrated. Activity of nitrergic nerves can be blocked by presynaptic action (Esplugues, 2002); this has been demonstrated to occur for example via alpha-adrenoceptors in the canine ileocolonic junction (Boeckxstaens et al, 1993), via muscarinic receptors on cerebral perivascular nitrergic nerves (Liu et al, 2002) and varicosities of serotonergic interneurons have been shown to appose nitrergic neurons in the guinea pig small intestine (Neal and Bornstein, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Transient presynaptic inhibition of nitrergic nerves could be responsible for this, although this has never been demonstrated. Activity of nitrergic nerves can be blocked by presynaptic action (Esplugues, 2002); this has been demonstrated to occur for example via alpha-adrenoceptors in the canine ileocolonic junction (Boeckxstaens et al, 1993), via muscarinic receptors on cerebral perivascular nitrergic nerves (Liu et al, 2002) and varicosities of serotonergic interneurons have been shown to appose nitrergic neurons in the guinea pig small intestine (Neal and Bornstein, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to explain this discrepancy, although some of previous findings seemed to support the results of this study. [32][33][34][35][36][37][38] Decreased rectal compliance is an important pathophysiologic factor in some patients with incontinence because of the lack of rectal reservoir function, especially if they also have another factor, such as a weak anal sphincter. Substantial decreases in compliance are associated with an increased frequency of stools, rapid transit of stool through the rectum, and increased risk of fecal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…NO has been linked to the release (Meffert et al ., 1996) of other neurotransmitters and the effects which they produce, in particular acetylcholine (Gustafsson et al ., 1990; Li & Rand, 1989b), noradrenaline (Boeckxstaens et al ., 1993; Li & Rand, 1989a) dopamine (Hanbauer et al ., 1992), glutamate (Montague et al ., 1994; Sorkin, 1993), γ‐aminobutyric acid (GABA) (Beltran et al ., 1999; Kuriyama & Ohkuma, 1995), serotonin (Bogers et al ., 1991; Reiser, 1990b), adenosin triphosphate (ATP) (Boeckxstaens et al ., 1991a), bombesin (Beltran et al ., 1999), carbon monoxide (Xue et al ., 2000), opioids (Barnette et al ., 1990) and endothelin (Reiser, 1990a). The mechanisms responsible for these interactions are still not fully understood, but direct S‐nitrosylation of receptors, activation of cyclic GMP‐dependent protein phosphorylation cascades, regulation of neuronal energy dynamics and a modulating effect on transporters are potentially involved (Choi et al ., 2000; Kiss & Vizi, 2001; Pieper et al ., 2000).…”
Section: Signallingmentioning
confidence: 99%